2012
DOI: 10.1007/s11325-012-0792-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and sleep patterns in relation to consumption of energy drinks, caffeinated beverages, and other stimulants among Thai college students

Abstract: Purpose Poor sleep and heavy use of caffeinated beverages have been implicated as risk factors for a number of adverse health outcomes. Caffeine consumption and use of other stimulants are common among college students globally. However, to our knowledge, no studies have examined the influence of caffeinated beverages on sleep quality of college students in Southeast Asian populations. We conducted this study to evaluate the patterns of sleep quality; and to examine the extent to which poor sleep quality is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
4
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 42 publications
14
127
4
8
Order By: Relevance
“…Stimulant use was found to be statistically significant and positively associated with poor sleep quality. 10 Another study done on selected group of students in a University of life sciences, Poland showed that students consumed many more energy drinks during examinations (1424±1577 ml/week) than during the academic year (441±579 ml/week).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulant use was found to be statistically significant and positively associated with poor sleep quality. 10 Another study done on selected group of students in a University of life sciences, Poland showed that students consumed many more energy drinks during examinations (1424±1577 ml/week) than during the academic year (441±579 ml/week).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally appealing to this population due to its ability to help cope with the daytime sleepiness ubiquitous during the second decade of life [84]. Caffeine intake, is known to be associated with sleep difficulties, interruptions in the normal sleep cycles, and longer sleep onset latencies amongst adolescents [85,86], thereby potentially causing a vicious cycle in which the consumption of caffeine prevents the adolescent from sleeping at night, leading to elevated caffeine consumption during the day as a result of the consequent daytime sleepiness.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…We appreciate the thoughtful comments by Dr. Wiwanitkit on our article [1], in which we evaluated the patterns of sleep quality in relation to caffeine use among Thai college students. His commentary raises important issues.…”
Section: Dear Editormentioning
confidence: 99%